The Impact of the Covid-19 Pandemic on Financial Performance: Evidence from State-Owned Infrastructure and Non-Infrastructure Companies Listed on the Indonesia Stock Exchange - Muhammad Yunus Kasim; Muslimin; Husnah; Vitayanti Fattah; Munawarah; Adriyani Marwah (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze and compare the performance of SOEs in the infrastructure and non-infrastructure sectors listed on the Indonesia Stock Exchange (IDX) for the 2019–2021 period. The method used is quantitative descriptive with secondary data in the form of annual performance values and corporate health predicates based on the assessment set. The results show that the performance of infrastructure SOEs fluctuated with a significant decrease in 2020 (50.68) due to the COVID-19 pandemic, then recovered in 2021 (55.05) in line with government stimulus and the acceleration of strategic projects. Meanwhile, non-infrastructure SOEs also recorded a sharp decline in 2020 (43.75) and experienced a slower recovery in 2021 (49.82), not yet reaching pre-pandemic levels. Comparatively, infrastructure SOEs consistently have higher performance values than non-infrastructure throughout the observation period. Based on a three-year average, both sectors are in the